The SBL commentary on the Septuagint: an introduction - Büchner, Dirk (Septuagint and cognate studies, 2017)
"This book contains eight scholars' contributions of verse by verse commentary on the Greek text of the Hebrew Bible known as the Septuagint. Each chapter is from a different bible book, for which there will eventually be a full commentary published in the Society of Biblical Literature Commentary on the Septuagint. The commentary series focuses on the actual process of translation, so its authors try to describe